Chiral analysis of methadone and its major metabolites (EDDP and EMDP) by liquid chromatography–mass spectrometry - Kelly, Tamsin; Doble, P.; Dawson, M. (Elsevier, 2005)
Racemic methadone (MET) is administered to heroin users undergoing methadone maintenance therapy (MMT) in Australia. The enantiomers of methadone possess different pharmacological effects, and the enantioselective metabolism of methadone to its two major metabolites, 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) and 2-ethyl-5-methyl-3,3-diphenyl-1-pyrroline (EMDP) has been demonstrated. Therefore, a stereoselective method capable of quantifying methadone, EDDP and EMDP in biological samples could be of benefit in the monitoring of MMT patients. In particular, the analysis of hair samples would provide a means by which long-term monitoring of MMT patients could be achieved. To date, no HPLC method has been published for the simultaneous separation of the six enantiomers. A liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for the chiral analysis of methadone, EDDP and EMDP was developed using an -glycoprotein (AGP) stationary phase. The method development involved the utilisation of factorial analysis experimental designs and the application of artificial neural networks (ANNs) to model the chromatographic response surfaces. The optimal conditions were determined to be 20mM acetic acid: isopropanol (93:7, pH 7.4), with a flow rate of 0.9 mL/min. The method was validated and subsequently applied to the analysis of 20 hair samples collected from MMT patients.